Clinical Risk Factors Associated with Miscarriage - Aneela Gul Shaikh, Nusrat Lakho, Sabahat Fatima Shah (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: To identify the risk factors in patient came in OPD and in emergency with sign and symptoms of miscarriage. Method: Retrospective Cross Sectional was conducted at the Department of Obstetrics & Gynaecology, Lady Willingdon Hospital Khairpur Medical College Khairpur Mir’s from 1st January 2021 to 31st December 2022. Two thousand, one hundred and thirty patients of miscarriage were enrolled. Patient with congenital abnormal foetus and still birth were not included. Results: The majority of patients were more than 35 years of age was 974 (41%). It was also noted that abortion was more common in multigravida 1215 (57%). The risk factors of abortion were 1735 (81.4%) had lack of history of taking folic acid and multivitamins. Practical Implication: Poor socioeconomic status, lack of knowledge, illiteracy, marital problems, and physical abuse are significant risk factors for miscarriage, necessitating the provision of appropriate clinical and supportive information. Conclusion: The risk factors of miscarriage include age of mother, lack of history of taking folic acid and multivitamins during antenatal period increased body mass index and previous history of miscarriage physical abuses, history of infertility and h/o of smoking Berri and Hukka are significant. Keywords: Risk factors, Miscarriage, Outpatient Department, Incidence